Pneumolysin activates the NLRP3 inflammasome and promotes proinflammatory cytokines independently of TLR4. - Lavelle, Edward; Moran, Barry; Mc Loughlin, Rachel (My University, 2010)
Pneumolysin (PLY) is a key Streptococcus pneumoniae virulence factor and potential candidate for inclusion in pneumococcal subunit vaccines. Dendritic cells (DC) play a key role in the initiation and instruction of adaptive immunity, but the effects of PLY on DC have not been widely investigated. Endotoxin-free PLY enhanced costimulatory molecule expression on DC but did not induce cytokine secretion. These effects have functional significance as adoptive transfer of DC exposed to PLY and antigen resulted in stronger antigen-specific T cell proliferation than transfer of DC exposed to antigen alone. PLY synergized with TLR agonists to enhance secretion of the proinflammatory cytokines IL-12, IL-23, IL-6, IL-1?, IL-1? and TNF-? by DC and enhanced cytokines including IL-17A and IFN-? by splenocytes. PLY-induced DC maturation and cytokine secretion by DC and splenocytes was TLR4-independent. Both IL-17A and IFN-? are required for protective immunity to pneumococcal infection and intranasal infection of mice with PLY-deficient pneumococci induced significantly less IFN-? and IL-17A in the lungs compared to infection with wild-type bacteria. IL-1? plays a key role in promoting IL-17A and was previously shown to mediate protection against pneumococcal infection. The enhancement of IL-1? secretion by whole live S. pneumoniae and by PLY in DC required NLRP3, identifying PLY as a novel NLRP3 inflammasome activator. Furthermore, NLRP3 was required for protective immunity against respiratory infection with S. pneumoniae. These results add significantly to our understanding of the interactions between PLY and the immune system.
PUBLISHED
Keywords: Immunology; Pneumolysin; Biochemistry; Immunology, Inflammation & Infection